PENGARUH STRUKTUR KEPEMILIKAN, FINANCIAL DISTRESS DAN AUDIT TENURE PADA KETEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN - Narayana, Dewa Gede Agus; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
Financial statements and its delivery to public in timely manner is a qualitative characteristics of information for the achievement of  relevance  information. Timeliness in publication of company's financial statements may result in the increase users' trust in financial statements information. This study has objective to obtain empirical evidence of influence of the ownership structure, financial distress and audit tenure on timeliness of financial statements publication. Which is used as the study population is all that  ninth-sector companies listed on Indonesia Stock Exchange, method of determining sample is probability sampling, particularly proportionate stratified random sampling in the period 2012-2014. Obtained sample of 216 companies with 249 observations and then the analysis was done by using multiple linear regression. Analysis results showed that managerial ownership and tenure audit does not affect the timeliness of the financial statements publication. Institutional ownership and financial distress affects the timeliness of financial statements publication.
Keywords: financial distress, audit tenure, ownership structure, the timeliness of publication of financial statements.